Generation Cogeneration [the data]. - Patel-Predd, P. (IEEE spectrum)
Coal and natural-gas power plants lose as waste heat two-thirds of the energy they produce. Combined-heat-and-power (CHP) systemsÃ?Â¿what used to be called cogeneration-attain 80 percent efficiency by capturing the heat and using it locally. CHP predates electrical grids in many parts of the world.